Pengaruh Kualitas Informasi dan Kemudahan Penggunaan Website BTN Property For Developer Terhadap Efisiensi Biaya Operasional Pada Developer Kota Palembang - Dahlia; Arisman, Anton (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2025)
The property sector in Indonesia is rapidly expanding, with demand for landed houses driving housing needs. One solution to facilitate affordable housing is through the government-subsidized Home Ownership Credit (KPR). The BTN Property for Developer website has provided developers with an efficient platform to manage projects. This study aims to examine the impact of information quality and user-friendliness of the BTN Property for Developer website on the operational cost efficiency of developers in Palembang City. Accurate, relevant information and a simple, accessible system play a crucial role in reducing operational costs and improving productivity. This quantitative study uses non-probability sampling, specifically saturated sampling, with 70 developers actively using the website as participants. Data were collected via questionnaires and analyzed with SPSS software. The findings indicate that both the quality of information and ease of use positively affect operational cost efficiency. The better the information quality and the easier the website’s use, the more efficient the operational costs. Additionally, these factors collectively contribute to improving operational cost efficiency. Keywords: Property industry, Home Ownership Credit (KPR), Information Quality, Ease Of Use, Operational Cost Efficiency.